2017
DOI: 10.1055/s-0043-101683
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for inadequate bowel preparation: a validated predictive score

Abstract: Inadequate bowel cleansing negatively affects the efficiency of colonoscopy in routine clinical practice. The aim of this study was to design and validate a predictive model for inadequate bowel cleanliness. The model was built from 667 consecutive outpatients (development cohort) who were prospectively scheduled for colonoscopy between June and September 2014. The validation cohort included 409 outpatients who underwent colonoscopy between October and December 2014. Cleansing was evaluated using the Boston Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(83 citation statements)
references
References 22 publications
4
56
1
2
Order By: Relevance
“…There is agreement that there are three main explanations for post-colonoscopy CRC: missed advanced neoplasia, new lesions and incompletely resected lesions. The most important factor related to missed advanced neoplasia is the ADR, which in turn depends on cecal intubation rate, withdrawal time, and colon cleansing 15 18 21 22 23 24 25 26 27 . All these factors are interrelated.…”
Section: Discussionmentioning
confidence: 99%
“…There is agreement that there are three main explanations for post-colonoscopy CRC: missed advanced neoplasia, new lesions and incompletely resected lesions. The most important factor related to missed advanced neoplasia is the ADR, which in turn depends on cecal intubation rate, withdrawal time, and colon cleansing 15 18 21 22 23 24 25 26 27 . All these factors are interrelated.…”
Section: Discussionmentioning
confidence: 99%
“…Current studies have shown that adequate bowel preparation is related to the following factors: type of diet and laxatives, time between taking the last laxative dose and the colonoscopy, ability to comply or tolerate bowel preparation, and non-split dose or split dose of laxatives. [ 2 3 4 5 ] Limiting the type of diet can reduce the amount of stool in the intestines. Previously, it was a common practice to limit patients to a clear liquid diet (CLD) for 1 day before colonoscopy, but this practice significantly increased the hunger sensation of patients, greatly reduced patient compliance and comfort, and even caused hypoglycaemia.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, family history of CRC or personal history of polyps have been associated with better quality of bowel cleansing attributed to a higher motivation (29). Moreover, conditions associated with delayed colonic transit such as constipation (5, 49, 50), altered bowel anatomy due to previous abdominal or pelvic surgery (5) (including colorectal resection, mainly left resections) (5, 47, 51), drugs (tricyclic antidepressant, opioids or calcium antagonists) (5, 49), or comorbidities such as diabetes (5, 29, 47, 49) have been reported to be risk factors for inadequate bowel preparation. Physical activity restrictions due to obesity (47) and comorbidities have also been reported to be risk factors for poor bowel cleansing (5).…”
Section: How Can We Improve Bowel Preparation Quality?mentioning
confidence: 99%
“…However, up to 30% of diagnostic colonoscopies are reported to have an inadequate bowel cleasing (4). Recently, several studies have assessed risk factors associated with an inadequate bowel preparation, suggesting that more research is warranted on new strategies to improve bowel cleansing (5). This review aimed to analyze these recommendations, placing special attention on patients that have an increased risk of inadequate bowel preparation.…”
Section: Introductionmentioning
confidence: 99%